2020
DOI: 10.21203/rs.3.rs-69908/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sex Differences in Association Between Body Composition and Frailty or Physical Performance in Community-Dwelling Older Adults

Abstract: BackgroundFrailty is a common geriatric condition due to aging, defined as a decrease in the functional reserve to maintain the homeostasis. As part of the aging process, body composition changes occur. This study investigated the relationship between body composition and frailty in a community-dwelling elderly Korean population.MethodsThis cross-sectional cohort study analyzed data of 2,385 elderly participants (aged 70–84 years, 1131 males and 1254 females) of the Korean Frailty and Aging Cohort Study from 2… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…Kim et al [33] reported a positive association between muscle mass indices and physical performance status in only weak populations. Muscle mass is positively associated and intramuscular or intermuscular fat is inversely associated with strength or physical performance [34–36] . Muscle dysfunction, such as strength and performance, can be determined earlier compared with decreased in muscle mass; this may be associated with the increased inter- and intra-muscular fat infiltration [37–39] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al [33] reported a positive association between muscle mass indices and physical performance status in only weak populations. Muscle mass is positively associated and intramuscular or intermuscular fat is inversely associated with strength or physical performance [34–36] . Muscle dysfunction, such as strength and performance, can be determined earlier compared with decreased in muscle mass; this may be associated with the increased inter- and intra-muscular fat infiltration [37–39] .…”
Section: Discussionmentioning
confidence: 99%
“…Muscle mass is positively associated and intramuscular or intermuscular fat is inversely associated with strength or physical performance. [34][35][36] Muscle dysfunction, such as strength and performance, can be determined earlier compared with decreased in muscle mass; this may be associated with the increased inter-and intra-muscular fat infiltration. [37][38][39] In our cohort, the female participants had less muscle mass and greater muscular fat compared with men.…”
Section: Discussionmentioning
confidence: 99%
“…In the article, “Sex differences in association between body composition and frailty or physical performance in community-dwelling older adults”, [ 1 ] which appeared in Volume 100, Issue 4 of Medicine , the rows in Tables 4 and 5 were not correctly aligned. The correct tables are below.…”
mentioning
confidence: 99%